Pengaruh Latihan Pursed Lips Breathing Terhadap Respiratory Rate Pada Pasien TB Paru Di Ruangan Anggrek RS TK II Robert Wolter Mongisidi Manado - Abdul Wahid Siokona; Zainar Kasim; Rahmat Hidayat Djalil (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
This study focuses on the impact of Pursed Lips Breathing (PLB) exercises on the Respiratory Rate (RR) of Pulmonary Tuberculosis (TB) patients. Tuberculosis, caused by Mycobacterium tuberculosis bacteria, often leads to abnormal breathing patterns. The objective of this research is to determine the influence of Pursed Lips Breathing (PLB) exercises on the RR of TB patients. The research methodology employs a pre-experimental design with a One group Pretest-Posttest Design. The study includes a population of 30 respondents, and a total sample of 30 respondents selected through total sampling technique. Research instruments consist of observation sheets, SOP, and a Stopwatch. Data analysis utilizes the Dependent T-test. The study's findings indicate a significant impact of PLB exercises on the RR of TB patients, with a p-value of 0.000 (? ? 0.05). This underscores the importance of considering PLB exercises as an effective alternative therapy for managing changes in respiratory rate. Furthermore, it can be applied by families at home, ensuring that the therapy's benefits are more widely realized.